2016
DOI: 10.1097/aog.0000000000001422
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Endometriosis During Abdominal or Laparoscopic Hysterectomy for Chronic Pelvic Pain

Abstract: Fewer than 25% of women undergoing laparoscopic or abdominal hysterectomy for chronic pelvic pain have endometriosis at the time of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 26 publications
2
53
0
2
Order By: Relevance
“…Worldwide prevalence rates range between 5.7 and 26.6% [2]. Endometriosis is the presence of endometrial tissue outside the uterine cavity and is the most common cause of CPP [3] with 24 to 40% of women with CPP diagnosed with endometriosis [4, 5]. Endometriosis-related CPP includes a variety of pain symptoms including dysmenorrhea (period pain), dyspareunia (pain during sexual intercourse), dyschezia (pain on bowel motions) and dysuria (pain on urination).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide prevalence rates range between 5.7 and 26.6% [2]. Endometriosis is the presence of endometrial tissue outside the uterine cavity and is the most common cause of CPP [3] with 24 to 40% of women with CPP diagnosed with endometriosis [4, 5]. Endometriosis-related CPP includes a variety of pain symptoms including dysmenorrhea (period pain), dyspareunia (pain during sexual intercourse), dyschezia (pain on bowel motions) and dysuria (pain on urination).…”
Section: Introductionmentioning
confidence: 99%
“…The data was based on assessments given by experienced senior consultants working in centers which participated in QS ENDO Real and suggests that many measures recommended as the gold standard of treatment in national and international guidelines are not being implemented in the DACH region. Assuming that the participating centers are institutions which at least engage with the clinical picture and symptoms of endometriosis and are involved in promoting the best possible treatment, then the percentage of centers implementing recommended measures in the other 2 2 ⁄3 3 of departments is likely to be considerably lower.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis affects approximately 10-15 % of premenopausal women [1,2]. Patients commonly suffer from cycle-related pain but also report non-cycle-related discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…8 A recent retrospective cohort study showed that prevalence of endometriosis in all patients undergoing abdominal or laparoscopic hysterectomy was approximately 15.2% and within chronic pelvic pain patients, 21.4% were noted to have endometriosis; patients with anticipated endometriosis had 42.8% confirmed postsurgically. 9 In another study of chronic pelvic pain patients treated surgically, endometriosis was present in 33%. 4 There is poor correlation between operative findings and histopathological diagnosis with a positive predictive value as low as 45% according to one study.…”
mentioning
confidence: 97%
“…These findings further increase the complexity of establishing a clear relationship between endometriosis and chronic pelvic pain as its sentinel symptom. 9,11 Therapies for endometriosis are directed mostly at symptomatic relief and will be discussed in more detail in a separate review. Typically, initial treatment of presumed endometriosis entails conservative medical therapy such as nonsteroidal anti-inflammatory drugs (NSAIDs) or hormonebased therapy such as combined estrogen and progestin methods, progestin-only methods, and gonadotropin-releasing hormone (GnRH) agonists.…”
mentioning
confidence: 99%